2020
DOI: 10.1186/s13046-019-1511-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of miR-15b-3p enhances tumorigenesis and malignant transformation through the DYNLT1/Caspase-3/Caspase-9 signaling pathway in gastric cancer

Abstract: Background: Exosomes are essential for tumor growth, metastasis, and are used as novel signaling molecules in targeted therapies. Therefore, exosomal miRNAs can be used in new diagnostic and therapeutic approaches due to their involvement in the development of cancers. However, the detailed biological function, potential molecular mechanism and clinical application of exo-miR-15b-3p in gastric cancer (GC) remains unclear.Methods: miR-15b-3p mRNA levels in tissues, serum, cells and exosomes were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 63 publications
(70 reference statements)
3
55
0
Order By: Relevance
“…43 Wei et al indicated that gastric cancer cell-derived exosomal miR-15b-3p led to the malignant transformation of gastric mucosa epithelium cells, promoting cell proliferation and migration. 28 In this study, we found that exosomal hsa_circ_0000069 is secreted by SW1990 cells that can be internalized by HPDE cells. In addition, functional experiments demonstrated that SW1990 cell-derived exosomes promoted the proliferation, migration and cell cycle progression of HPDE cells; however, these changes were reversed by exosomes with downregulated hsa_circ_0000069.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…43 Wei et al indicated that gastric cancer cell-derived exosomal miR-15b-3p led to the malignant transformation of gastric mucosa epithelium cells, promoting cell proliferation and migration. 28 In this study, we found that exosomal hsa_circ_0000069 is secreted by SW1990 cells that can be internalized by HPDE cells. In addition, functional experiments demonstrated that SW1990 cell-derived exosomes promoted the proliferation, migration and cell cycle progression of HPDE cells; however, these changes were reversed by exosomes with downregulated hsa_circ_0000069.…”
mentioning
confidence: 61%
“…Wei et al found that exosomal miR-15b-3p was found to be secreted by gastric cancer cells, promoting malignant transformation of gastric mucosa epithelium cells. 28 We then focused on whether exosomal hsa_circ_0000069 involved in the communication between SW1990 cells and HPDE cells. To determine whether SW1990 cellderived exosomes were internalized by HPDE cells, the exosomes were labeled with PKH26 and incubated with HPDE cells.…”
mentioning
confidence: 99%
“…The overexpression of miR-15b has been confirmed in ovarian cancer 24 and gastric cancer. 25 Moreover, upregulation of miR-15b has been established to promote the resistance of renal cell carcinoma cells to sunitinib. 26 While in tissues collected from patients with highly aggressive BC, the overexpression of miR-15b was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the three miRNAs have potential to be prognostic biomarkers in COAD as well. It is reported that other four miRNAs, miR-29c-5p, miR-15b-3p, miR-130a-3p, and miR-500a-3p, were associated with various cancers but not recommended as prognostic markers [ 30 33 ]. Our results suggest that those DEMs (miR-144-5p, miR-145-5p, miR-486-5p, miR-29c-5p, miR-15b-3p, miR-130a-3p, and miR-500a-3p) may serve as potential biomarkers, but their feasibility remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%